Comorbidity of diseases of the cardiovascular system and diseases of the digestive organs with changes in organs and tissue of the oral cavity - Dmitry I. Trukhan; Larisa Yu. Trukhan; Darya S. Ivanova (LLC "MEDIAFORMAT", 2021)
Currently, in most clinical cases, the patient has a concomitant or combined pathology described by the terms "polymorbidity" (in the absence of a pathogenetic relationship) and "comorbidity" (in the presence of a pathogenetic relationship) between various diseases and pathological conditions. In the system of relationships between an internist and physicians of other specialties, the least studied aspects of their clinical interaction with a dentist. At the same time, often the reason for a patient's visit to the dentist is the presence of somatic pathology, and for the most part, not completely healthy patients come to the dentist's appointment, whose problems are limited to the oral cavity. On the other hand, the presence of certain changes in organs and tissues of the oral cavity and the advice of a dentist can help the internist in the diagnosis and adequate treatment of the patient. The first part of the presented review examines possible changes in the organs and tissues of the oral cavity in patients with diseases of the cardiovascular system and diseases of the digestive system. The second part of the review is devoted to the analysis of the possible effect on the organs and tissues of the oral cavity of drugs used to treat cardiovascular and gastroenterological diseases.